Post-Islamism and the Remaking of Islamic Public Sphere in Post-reform Indonesia - Ansor, Muhammad (Studia Islamika, 2016)
The following essay examines post-Islamism in post-reform Indonesia by focusing on contestation in the remaking of the Islamic public sphere. I argue that the public sphere is not only an arena of contestation between Islamists and secularists, but also among the proponents of social movements that mobilize Islam as a source of legitimacy. In the first section, I present a brief review of the notion of post-Islamism and Islamic public sphere as categories of analysis to examine the dynamics of Islam in Indonesia. Next, I explain the topography of Islamic movements in contemporary Indonesia. Post-Islamist contestation in the remaking of the Indonesian Islamic public sphere is examined in the third section. It is limited to four topics, i.e. the dynamics of Muslim intellectual movements, post-Islamist women’s activism and piety movements, Islamic visibility in pop culture, and discourses of shari’a implementation in Aceh. Finally, the article concludes that the dynamics of Indonesian post-Islamists and their contestation are not only helping to strengthen the praxis of democracy in the post-reform era, but they are also diverting public attention from the temptation of radicalism and violence in the name of religion.DOI: 10.15408/sdi.v23i3.2412